Anxiety disorder symptoms at age 10 predict eating disorder symptoms and diagnoses in adolescence - Schaumberg, Katherine (J Child Psychol Psychiatry, 2018)
BACKGROUND: Cross-sectional associations between anxiety disorders and eating disorders (EDs) have been well documented; however, limited research has examined whether symptoms of anxiety disorders are prospectively associated with EDs. Identifying these longitudinal associations can aid in discerning relationships among these, often comorbid conditions and point towards a mechanistic understanding of developmental psychopathology. The current study investigated the prospective associations between parent-reported anxiety in mid-childhood (age 10) and child-reported ED behaviors and disorders in adolescence (at ages 14 and 16 years) in a population-based sample. METHODS: Participants were individuals enrolled in the Avon Longitudinal Study of Parents and Children (ALSPAC), a population-based, prospective study of women and their children; 7,767 children whose parents provided data at age 10 were included in current analyses. An exploratory factor analysis identified latent anxiety factors at age 10, followed by a path analysis that evaluated associations between these factors and eating disorder symptoms and cognitions at age 14. RESULTS: Parent-reported anxiety symptoms at age 10 yielded 5 factors: obsessive-compulsive disorder (OCD) symptoms related to symmetry and checking (Factor 1); OCD symptoms associated with aversion to dirt and germs (Factor 2); physical anxiety symptoms (Factor 3); worries (Factor 4); and social phobia symptoms (Factor 5). Factors 3 and 4 showed the most consistent, positive associations with a range of ED symptoms at age 14. Factor 3 predicted diagnosis of bulimia nervosa by age 16 (OR = 1.11, p = 0.007), while Factor 4 predicted diagnoses of anorexia nervosa (OR = 1.10, p = 0.01) and disordered eating by age 16 (OR = 1.08, p = 0.001). CONCLUSIONS: Results indicate that symptoms of generalized anxiety in middle childhood may predict adolescent-onset ED symptoms and ED diagnoses.